Exploring Social and Cultural Meanings in the Novel Tempurung by Oka Rusmini: Its Relevance to Literature Learning in Senior High School - Dewi, Ni Luh Candra; Yarsama, I Ketut; Sujaya, I Made (Jurnal Paedagogy, 2026)
This study aims to analyze the representation of social and cultural meanings in the novel Tempurung by Oka Rusmini and to examine its relevance as literature learning material for senior high school students. The study employed a qualitative approach using a descriptive-interpretative method. The primary data consisted of textual elements in the novel, including words, phrases, sentences, dialogues, narrative passages, characters’ actions, and significant events. Supporting data were obtained from the Merdeka Curriculum documents, particularly the Indonesian Language Learning Outcomes for Phase F, as well as qualitative responses from Indonesian language teachers and Grade XI/XII students collected through focus group discussions (FGDs), interviews, and open-ended questionnaires. The data were analyzed using descriptive-interpretative content analysis. The findings indicate that the novel represents a range of social meanings, including social stratification, gender inequality, power relations, and tensions between individual agency and collective social norms. Its cultural meanings are reflected through religious beliefs, Balinese customs and traditions, the symbolic meaning of the Tempurung (coconut shell), family honor, social obligations, and the value of harmony. The findings further suggest that Tempurung is highly relevant as literature learning material for senior high school because it promotes critical reading, literary appreciation, social empathy, cultural awareness, and the strengthening of the Pancasila Student Profile.